A review of risk factors for hamstring injury in soccer: a biomechanical approach - Enrique Navarro Cabello; David Chorro Hernández; Gonzalo Torres Márquez; Carlos García González; Archit Navandar; Santiago Veiga González (Asociación Española de Ciencias del Deporte, 2015)
The aim has been to review the literature about the risk factors of hamstring injury in soccer from a biomechanical point of view. METHODOLOGY. Data bases of bibliography references were Medline, Scopus and SportDiscuss. RESULTS AND DISCUSSION. Many prospective studies have shown that the previous injury is the greatest risk factor of sustaining the injury. However the primary causes of the injury are unclear in soccer. A lack of hamstring flexibility has been one of the main injury risk factors with controversies on the results. Imbalance of isokinetic force is a risk factor but electrical coactivation of all muscles participating during knee flexion and extension are unknown in football. While the importance of lumbopelvic-hamstrings muscles synchronization during running seems to be crucial for understanding the risk of injury, no research has been developed in this topic in football. CONCLUSIONS. More research using new data recording procedures as Dynamic Scanners, Surface EMG, Inverse Dynamic Analysis are needed. The analysis of more specific movements as running, kicking or jumping is clearly required. Managers, coaches, physical trainers, physiotherapists, sport physicians and researchers should work together in order to improve the injury prevention and rehabilitation programs of football players.